NANOTECHNOLOGY TOWARDS ENVIRONMENTAL SUSTAINABILITY - Singh, M. K. (Journal of Dharma, 2014)
Nanotechnology has moved from the realm of science-fiction to reality at more than expected speed. Various areas in which nanotechnology presently seem to be having a decisive role to play is still in the state of tip of the iceberg and once it is exponentially deployed and employed there will be hardly any sphere of life which will not have a nano-touch in it and by that time world might be known as nano-world. With this at the backdrop the answer to the problem for sustenance of the planet will also have to come from nanotechnology. In the visible spectrum the planetary medicine aspect of artificial photo-synthesis seems to be the answer, once effectively arrayed on ground. If that is to be the case, the ethical aspect of its fructification will need to be conceptualized and formulated and global regulatory system will need to be put in place. Needless to say, either ethics will have to catch up with the galloping nano-technology or the latter will have to slowdown to be in empathy with the former, in the overall interest of humanity and that of the planet.